DIGITAL TRANSFORMATION OF THE HOTEL AND RESTAURANT BUSINESS: THE ROLE OF INFORMATION SYSTEMS IN SHAPING MODERN SERVICE - Панасенко, Наталія; Калашник, Олена; Тищенко, Олександр (Modern engineering and innovative technologies, 2025)
The paper examines current trends in the digitization of the hotel and restaurant business, which are leading to fundamental changes in management, service organization, and customer interaction. The integration of digital technologies into the activities